The Link Between Bacterial Inflammagens, Leaky Gut Syndrome and Colorectal Cancer - de Waal, Greta M; de Villiers, Willem J.S.; Pretorius, Etheresia (Current Medicinal Chemistry, 2021)
There is a causal relationship between cancer (including colorectal cancer), chronic systemic inflammation and persistent infections, and the presence of dysregulated circulating inflammatory markers. It is known that aberrant clot formation and coagulopathies occur in systemic inflammation. In colorectal cancer, there is a close link between gut dysbiosis and an inflammatory profile. In this review, we present evidence of the connection between gut dysbiosis, the entry of bacteria into the internal environment, and the presence of their highly potent inflammagenic molecules, such as lipopolysaccharide and lipoteichoic acid, in circulation. These bacterial components may act as one of the main drivers of the inflammatory process (including hypercoagulation) in colorectal cancer. We review literature that points to the role of these bacterial inflammagens and how they contribute to colorectal carcinogenesis. Insight into the factors that promote carcinogenesis is crucial to effectively prevent and screen for colorectal cancer. Early diagnosis of an activated coagulation system and the detection of bacterial components in circulation and also in the tumour microenvironment, could therefore be important, and may also, together with modulation of the gut microbiota, serve as potential therapeutic targets.
Keywords: inflammation